Analisis Kepuasan Kerja dan Budaya Organisasi Terhadap Pengaruh Kinerja Pegawai Bappedalitbang Kabupaten Bogor dengan Komitmen Organisasi sebagai Variabel Intervening - Gunawarman, Mohammad Irman; Slamet Ahmadi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
Human resources are the driving force for the overall management of a company in achieving its goals. So the effectiveness of a company in managing human resources greatly determines the success of the company. The current performance condition of BAPPEDALITBANG needs to be optimized again so that development planning in Bogor Regency can be as expected. The aim of this research is to determine the effect of job satisfaction on employee performance and organizational commitment on employee performance with commitment as an intervening variable. The research was carried out at BAPPEDALITBANG with a research population of 113 employees. The sample was determined using the Slovin formula to obtain a sample of 89 respondents. For data collection, the questionnaire method and direct observation were used. And to analyze the data using the Smart Partial Least Square (PLS) analysis method version 3.0, the data tests used in this research are reliability testing, validity testing, hypothesis testing and classical assumption testing. Based on the results of the research and discussion, several conclusions can be drawn, namely that there is a direct positive and significant influence of job satisfaction on employee performance, there is a direct positive and significant influence of job satisfaction on organizational commitment, there is a direct positive and significant influence of organizational culture on employee performance, there is a direct positive and significant influence from organizational culture on organizational commitment, there is a direct positive and significant influence from organizational commitment on employee performance, there is an indirect positive and significant influence from job satisfaction on employee performance, there is a positive and significant influence significant indirect impact of organizational culture on employee performance.